Mid-Carboniferous deglaciation of the Protoprecordillera, Argentina recorded in the Agua de Jagüel palaeovalley - Henry, Lindsey C.; Isbell, John L.; Limarino, Carlos Oscar; McHenry, Lindsay J.; Fraiser, Margaret L. (Palaeogeography, Palaeoclimatology, Palaeoecology)
The Agua de Jagüel Formation near Uspallata, Mendoza Province, Argentina, was deposited within a palaeovalley along the southeastern margin of the Calingasta-Uspallata Basin adjacent to the Protoprecordillera. The basal glacigenic sequence of the formation was deposited in the Serpukhovian-Early Bashkirian, near the beginning of the late Palaeozoic ice age. The sequence is composed of diamictite, conglomerate, sandstone, and mudrock and records four depositional stages within a palaeofjord: 1 morainal bank deposition by a wet-based tidewater glacier, 2 glacial retreat succession where ice retreated up the fjord out of the immediate area, allowing iceberg deposition of dropstones and dump deposits, 3 continued glacial retreat with ice receding onto land, allowing a shoreface to develop within the palaeovalley, and 4 transgression across the shoreface and resumption of iceberg deposition. The thickness and facies of this succession are similar to deposits within modern Alaskan fjords housing temperate tidewater glaciers. Comparison of the Agua de Jagüel Formation with Alaskan fjords indicates that sequence stratigraphy used for low latitude deposits must be applied with caution, as glacimarine ice retreat within a fjord produces strata surfaces that are easily misidentified as flooding surfaces resulting from changes in water depth. Likewise, the transgression during stage 4 is significant as it indicates a rise in sea level that occurred during glaciation of the Protoprecordillera, thus suggesting that the transgression between stages 3 and 4 was not driven by input of glacial meltwater. Additionally, the sediment geochemistry suggests that the bottom waters of the palaeovalley were anoxic, which may help explain the absence of bioturbation in the sequence as well as in other ancient glacimarine palaeovalleys. The deglaciation succession and transgression are also recorded in the nearby Hoyada Verde and Tramojo Formations, so it is proposed that all three formations record one glacial event in the ...